Partial range of motion resistance training: a feasible bodybuilding training regimen for local or regional muscle hypertrophy?: Erratum - Newmire, D. E.; Willoughby, D. S. (Strength and Conditioning Journal, 2020)
In "Partial Range of Motion Resistance Training: A Feasible Bodybuilding Training Regiment for Local or Regional Muscle Hypertrophy?" published in the October 2020 issue a typo in the title was identified, and the article has been updated online.